Surgical Weight Loss to Treat Atrial Fibrillation Risk and Progression - Nalliah, C. J.; Sanders, P.; Kalman, Jonathan M. (Current cardiovascular risk reports, 2017)
Purpose of Review This review aims to examine the breadth of data associating atrial fibrillation (AF) with obesity at epidemiologic, mechanistic, and clinical levels. We then proceed to place surgical weight loss within that context. Recent Findings Epidemiologic studies have demonstrated a robust correlation between overweight and AF. Various mechanistic factors including concomitant risk factors, diastolic impairment, inflammation, and pericardial fat have been observed to contribute to the atrial substrate for AF. However, weight loss can institute a process of reverse atrial remodeling improving arrhythmias profile. Thus, weight loss has emerged as an indispensable aspect of effective AF management. Yet, effective weight management is often a challenging and frustrating journey for clinician and patient, raising surgical weight loss as a potential option. However, data on the role of surgical weight loss on AF are limited. Observations indicate that the dramatic and sustained weight loss availed by surgical intervention may be capable of attenuating rates of incident AF. The impact of surgical weight loss on AF populations remains unknown. However, it is likely that most of the antiarrhythmic benefits of non-surgical weight loss would be paralleled in surgical candidates, mediated by similar mechanisms. Surgical weight loss has been associated with reverse structural remodeling, improvement of diastolic function, and modulation of the autonomic profile. Summary There exists a compelling case for the utilization of surgical weight loss to circumvent the obstacle of treatment failure. However, resort to an invasive procedure with antedant risks for AF management alone would be premature in the absence of robust data. However, it may find a more immediate role in the context of AF ablation, where exposure to procedural risk must be justified by optimizing procedural success. Further data surrounding surgical weight loss and its antiarrhythmic benefits are required to define its role in the battle against the dual and closely linked epidemics of AF and obesity. Surgical weight loss would be a powerful weapon in the clinician’s armamentarium that would further consolidate weight loss as the fourth pillar of AF management.